Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar - Ríos, Pilar (2021)
This database includes information on porífera collected during several Spanish Antarctic expeditions: Bentart 94; Bentart 95; Gebrap 96; Ciemar 99/00 and Bentart 2003. The expeditions focused from the Antarctic Peninsula to Bellingshausen Sea.Porifera were collected using rock dredge, Van Veen dredge, anchor dredge, suprabenthic sledge, fish traps, scuba diving, Box corer and Agassiz trawl.The dataset now reaches 771 occurrence data that have checked for systematic reliability. This database is not finished and the collection is growing. The data are available in Gbif.